Exploration of Students' Conceptual Understanding and Ethnophysics: A Case Study of Tifa In The Tanimbar Islands, Indonesia - John Rafafy Batlolona; Marleny Leasa; Pamella Mercy Papilaya; Jamaludin Jamaludin; Jony Taihuttu (Jurnal Penelitian Pendidikan IPA, 2022)
Contemporary culture has disturbed the local community's culture, which has been maintained since the time of the ancestors. The Tanimbar culture has been preserved and maintained. Tifa Tanimbar is a small musical instrument used for arts and cultural performances of the community. It is one of the heritage and wealth of an area different from other regions. This study shows something different, namely Tifa, in learning physics. This study aimed to analyze the conceptual physics of students based on ethnoscience on the Tifa concept in the Tanimbar Islands. The research was conducted in 10 elementary schools in the Tanimbar Islands Regency with 300 students with 175 male students and 125 female students. The questions given to test students' conceptual tests were physics diagnostic tests, totaling 6 questions. The study results informed that the average conceptual physics of students related to Tifa was 55.42. It indicates that the conceptual physics of elementary school students is still very weak with a good category. Therefore, there is a solution to develop ethnophysics-based teaching materials with orientation to local potentials affiliated with science in improving students' conceptual physics. This research implies that teachers can develop teaching materials that foster students' cognition with surrounding phenomena based on local culture